Pengaruh Pembelajaran Mind Map Terhadap Hasil Belajar Biologi Siswa Kelas X Di SMAN Kebakkramat Semester Genap Tahun Pelajaran 2015/2016 - Munandar, Rosyid Aris, Dra. Hariyatmi, M. Si (2016)
Make a note is one of the activities of students. The form of traditional outline note is less interesting or the activity of making a note is not impressive triggered the saturation of students during learning, it is very influenced the students on understanding the concept of lesson material. This research aims to discover the effect of mind map learning toward the biology learning result of tenth-grade in SMAN Kebakkramat on the second semester of 2015/2016 academic year. The research used true experiment method with posttest only control group design. The research population was tenth grade students. The sample data were taken from two class with cluster random sampling. The data collected by using final test (posttest) and data analysis was used in the research Independent Sample T-Test. Before the data were analyzed, the prerequisite test was conducted, which were normality and homogeneity test. In mind map learning the results was obtained with the average score was 82,74 and the rintas learning the average score was 78,92. Thus, it can be concluded that there is the effect of mind map learning toward the biology learning result of tenth-grade in SMAN Kebakkramat in the second semester 2015/2016 academic year.